Survey data for vascular plants in 240 plots inside and outside a 900 ha area with a deer exclusion fence in Nikko National Park, Japan - Petersson, Lisa; Jensen, Daniel; Salk, Carl; Ohkubo, Tatuhiro; Thor, Göran (Swedish University of Agricultural Sciences, 2025)
The data file contains 240 rows × 126 columns.
Forest stands and plot setup:
Study area:
24 forest stands identified (12 larch, 12 oak) in the southern portion of the fenced area.
Replicate stands:
Each stand paired with a replicate within 300 m on opposite sides of the fence; stands without replicates within this distance were excluded.
Plot establishment:
Total plots: 10 circular plots per stand = in total 240 plots (120 inside, 120 outside the fence).
Plot size:
Each plot covers 10 m², centered on a larch or oak tree.
Plot layout:
Plots were placed at least 10 m from other canopy trees (>30 cm DBH) to avoid influences from species other than larch and oak.
Data collection:
Dwarf bamboo:
Average height measured from five random points per plot.
Understory vascular plants:
All species, including trees and shrubs <1.3 m tall, recorded.
Species cover:
Measured using a modified Braun-Blanquet cover class system with seven cover categories.
Braun -Blanquet scale Cover range (%) Used in calculations (%)
r <0.1
+ 0.1 – 1
1 1 – 5
2 5 – 25
3 25 – 50
4 50 – 75
5 75 – 100
*For dwarf bamboo, which was very abundant, 100% cover was used for category 5. This did not affect the calculations.
Taxonomic groupings:
Grouped species:
Dwarf bamboos: Sasa spp. (S. kurilensis, S. nipponica, S. palmata, Sasamorpha borealis).
Graminoids: Carex, Juncus, Luzula, Poaceae.
Non-flowering specimens: Rosa, Rubus, Viola (excluding Viola tokubuchiana var. tokubuchiana which was registered separately).
Maple seedlings: Acer spp. (excluding A. rufinerve which was registered separately).
Birch seedlings: Betula (B. platyphylla var. japonica, B. ermanii).
Euonymus species: E. alatus, E. macropterus, E. sieboldianus (excluding vine E. fortunei).
Nomenclature:
Follows Wamei checklist version 1.10 (Yamanouchi 2022) https://gbif.jp/activities/checklist/wamei_checklist_110/

Datafilen innehåller 240 rader × 126 kolumner.
Urval av bestånd och placering av provytor:
Studieområde:
24 bestånd identifierades (12 lärkdominerade, 12 ekdominerade) i den södra delen av det inhägnade området.
Bestånd:
Varje bestånd parades med ett replikat inom 300 m på motsatta sidor av viltstängslet; bestånd där replikat saknades inom 300 meter uteslöts ur studien.
Provytor:
Totalt antal provytor:
10 cirkulära provytor per bestånd = totalt 240 provytor (120 innanför, 120 utanför stängslet).
Provytestorlek:
Varje provytor är 10 m² och är centrerad runt en lärk eller en ek.
Utlägg av provytor:
Provytor placerades minst 10 m från andra trädslag (än lärk och ek) (>30 cm DBH) för att undvika påverkan från andra arter än lärk och ek.
Datainsamling:
Dvärgbambu:
Medelhöjd mätt från fem slumpmässiga punkter per provyta.
Undervegetation av kärlväxter:
Alla arter, inklusive träd och buskar <1,3 m höga, registrerades.
Täckningsgrad av arter:
Mätt med ett modifierat Braun-Blanquet-täckningssystem med sju täckningskategorier.
Braun-Blanquet-skala Täckningsintervall (%)
r <0,1
+ 0,1 – 1
1 1 – 5
2 5 – 25
3 25 – 50
4 50 – 75
5 75 – 100
*För dvärgbambu, som var mycket vanligt förekommande, användes 100% täckning för kategori 5. Detta påverkade inte beräkningarna.
Taxonomiska grupperingar:
Grupperade arter:
Dvärgbambu: Sasa spp. (S. kurilensis, S. nipponica, S. palmata, Sasamorpha borealis).
Gräs och halvgräs: Carex, Juncus, Luzula, Poaceae.
Icke-blommande exemplar: Rosa, Rubus, Viola (förutom Viola tokubuchiana var. tokubuchiana som registrerades separat).
Lönnplantor: Acer spp. (förutom A. rufinerve som registrerades separat).
Björkar: Betula (B. platyphylla var. japonica, B. ermanii).
Benved: Euonymus (E. alatus, E. macropterus, E. sieboldianus, exklusive vinrankan E. fortunei).
Nomenklatur:
Enligt Wamei-checklist version 1.10 (Yamanouchi 2022) https://gbif.jp/activities/checklist/wamei_checklist_110/
Inventeringsdata för kärlväxter i 240 provytor innanför och utanför ett 900 ha stängslat område i Nikko nationalpark, Japan
Keywords: FOREST COMPOSITION/VEGETATION STRUCTURE; SPECIES COMPETITION; TEMPERATE DECIDUOUS FOREST; TEMPERATE CONIFEROUS FOREST; DEER/MOOSE; forest ecology; skogens ekologi; mountain forest; bergsskog; forest conservation; forest ecosystem; skogens ekosystem; temperate forest; tempererad skog; forest biodiversity; skogens biologiska mångfald; temperate forest; vascular plants; competitive exclusion; vascular plant species abundance; forest restoration; coniferous forest; forest ecosystem; species diversity; montane forest; oak forest; forest conservation; forest inventory; species interactions; forest ecology; skogens ekologi; forest floor; forest dynamics; forest structure; forest cover; plant species composition; vascular plant species; forest regeneration; vascular plant species coverage; Habitats and biotopes; Naturtyper och biotoper; Land use; Markanvändning; Protected sites; Skyddade områden; Soil; Mark; Species distribution; Arters utbredning; forest damage; skogsförstörelse; forest protection; skogsskydd (växtskydd); forest regeneration; skogsföryngring; forest vegetation; skogsvegetation; game management; viltvård; Cervidae; hjortdjur; forest ecology; skogsekologi; coniferous forests; barrskogar; temperate broadleaf and mixed forests; lövskogar; nature conservation; naturskydd; game fences; viltstängsel; vascular plants; kärlväxter; forest conservation; skogsskydd (naturskydd); deer; japan; Tracheophyta; kärlväxter; Botany; Botanik; Ecology; Ekologi; Forest Science; Skogsvetenskap; Fish and Wildlife Management; Vilt- och fiskeförvaltning; Environmental Sciences and Nature Conservation; Miljö- och naturvårdsvetenskap; Biota; Biologi och ekologi